2008
DOI: 10.1021/la803024h
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Diffusion in Cross-Linked, Ethanol-Swollen Poly(vinyl alcohol) Gels: Counter-Intuitive Results Reflect Microscopic Heterogeneities

Abstract: Oxygen diffusion coefficients have been determined in ethanol-swollen poly(vinyl alcohol), PVA, gels using a technique wherein oxygen sorption is optically monitored using singlet oxygen phosphorescence. Data were recorded as a function of the extent to which the PVA chains are chemically cross-linked using glutaraldehyde. Contrary to conventional expectation, the diffusion coefficients obtained increase with an increase in the extent of cross-linking. This observation is interpreted in terms of a cross-link-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This latter statement is likewise relevant for recent work in which singlet oxygen phosphorescence experiments were used to quantify oxygen diffusion coefficients in solvent-swollen gels. 238 Data thus recorded indicated that, as the extent of crosslinking in these polymers was increased, these materials became more heterogeneous and were characterized by a combination of dense domains and less-dense open ''channels'' through which oxygen could more readily move. Data such as these certainly appear relevant with respect to light-initiated reactions that alter intracellular morphology (e.g., the collapse of cytoskeletal proteins, Fig.…”
Section: Quantifying Oxygen's Diffusion Coefficientmentioning
confidence: 99%
“…This latter statement is likewise relevant for recent work in which singlet oxygen phosphorescence experiments were used to quantify oxygen diffusion coefficients in solvent-swollen gels. 238 Data thus recorded indicated that, as the extent of crosslinking in these polymers was increased, these materials became more heterogeneous and were characterized by a combination of dense domains and less-dense open ''channels'' through which oxygen could more readily move. Data such as these certainly appear relevant with respect to light-initiated reactions that alter intracellular morphology (e.g., the collapse of cytoskeletal proteins, Fig.…”
Section: Quantifying Oxygen's Diffusion Coefficientmentioning
confidence: 99%
“…Some recent studies of oxygen permeability in polymers have obtained ambiguous conclusions; one study found that the presence of cross-links in glassy PMMA moderately decreased the oxygen permeability, 33 whereas another study found that the oxygen permeability increased with increased cross-linking in ethanol swollen cross-linked PVA. 34 The formation and kinetics of O 2 ( 1 Δ g ) were monitored by time-resolved phosphorescence at 1270 nm (Fig. 7, panel A) and singlet oxygen sensitized delayed fluorescence (SODF) at 650 nm (Fig.…”
Section: Preparation Of the Photoactive Anion-exchange Materialsmentioning
confidence: 99%
“…Strong swelling capabilities of ethanol and toluene to PVA have been well documented in the literature. 65,66 Our results indicated that the swelling of composite nanofibers would become more substantial with the order of acetone, hexane, DCM, chloroform, toluene, and ethanol, and such an order could be related to the polarities and chemical structures of the solvents.…”
Section: ■ Results and Discussionmentioning
confidence: 75%